Administration Of Fear Through Symbols About Covid-19 In Indonesian Online News - NUGROHO, Eko; RITONGA, Rajab; JAMALULLAIL, Jamalullail (International Journal of Environmental, Sustainability, and Social Science, 2023)
The Covid-19 outbreak is a global fear. This fear is partly triggered by diverse media representation. Information containing representations of COVID-19 has the potential to reduce fear. However, in reality, representations through these symbols have the potential to be used by those in power to exercise their power, especially to get rid of their political opponents through representation. The representation of Habib Rizieq Shihab as a violator of health protocols is suspected to be an attempt by the authorities to eliminate his political opponents through fear of the COVID-19 outbreak in symbols spread in the media. This research wants to answer how the administration of fear in symbols regarding violations of the COVID-19 protocol by religious figures in the representation of Habib Rizieq Shihab in Indonesian online news. This research explores the concept and criticizes the concept of administration of fear, which is a construct from dromology-based theories by Paul Virilio. This research uses Barthes' textual semiotics method (Barthes' 5 codes), which analyzes several online news texts in Indonesia. From the results of the analysis, it is revealed that the media representation of Habib Rizieq Shihab is a form of administration of fear carried out by the authorities through symbols about COVID-19 in the media by constructing logistics of perception and environmental construction that represents Habib Rizieq based on fear of the epidemic and fear of Islam (Islamophobia).